An Evaluation of the Master’s degree in Education, Program in Educational Administration, Payap University by CIPP Model - Somsathan, Prapatsorn (Dhammathas Academic Journal, 2026)
This research aimed to evaluate the Master of Education Program in Educational Administration (New Curriculum, 2021) at Payap University using the CIPP Evaluation Model, which consists of four dimensions: Context, Input, Process, and Product. The target groups included 8 program administrators and lecturers, 15 students enrolled in the 2021 academic year, 4 supervising instructors, 15 mentor administrators, 15 graduate employers and supervisors, and 15 graduates who completed the program in the 2022 academic year. The research instruments consisted of semi-structured interview forms, focus group discussion records, two curriculum evaluation questionnaires, and a graduate achievement survey. The first questionnaire assessed the context, input, and process dimensions, while the second assessed the product dimension. Both questionnaires employed a five-point rating scale with reliability coefficients of 0.94 and 0.87, respectively. Data were analyzed using frequency, percentage, mean, standard deviation, and content analysis. The findings revealed that: (1) the overall evaluation of the Master of Education Program in Educational Administration was at a high level (M = 4.25). When considered by dimension, the context, process, and input dimensions were also rated at a high level, with mean scores of 4.28, 4.26, and 4.21, respectively. (2) The evaluation of the product dimension showed an overall rating at the highest level (M = 4.72). All aspects of program outcomes were rated at the highest level, with mean scores ranging from 4.56 to 4.85. The three highest-rated outcomes were commitment to good governance and service-mindedness (M = 4.85), lifelong learning capability (M = 4.80), and adaptability (M = 4.79), respectively.